Prospects for Forest Industries in Madhya Pradesh - Tiwari, D. N. (Indian Forester, 1968)
The Forest potential of Madhya Pradesh is high. There is great scope for development of forest based industries. The resources call for the expansion of existing industries in paper, pulp, newsprint and saw milling, etc. A number of new industries have been suggested like hard board, insulation board, matchwood and industries based on minor forest products. The fuller utilization of the existing raw material will increase the revenue of the State manifolds and Madhya Pradesh will be one of the richest states in India.